Queen Bee Acid 10H2DA Halts HCT-116 Cells’ Collective Migration via Elevation of E-Cadherin and β-Catenin - Milena M. Jovanović; Dejan Arsenijević; Dalibor Nikolić; Igor Saveljić; Dragana Šeklić (Chemistry Proceedings)
A particular interest in oncology has presented the migration of cancer cells, collective and individual, and the switch between these two types of motilities greatly complicates this disease and adds further complexity to therapeutic approaches. Intercellular connections play a prominent role in motility, especially E-cadherin and β-catenin markers. Unsaturated fatty acid 10HDA has not been investigated so far on the collective migration of colorectal carcinoma (CRC) cells and components of intercellular junctions. Our study highlights the prominent anti-migratory effects of 10H2DA on HCT-116 cells, obviously due to the significant increase in E-cadherin and β-catenin protein expression, which are crucial targets in cancer treatment, and therefore should be extensively analyzed. In conclusion, 10H2DA presents a valuable source of anticancer potential worthy of further investigation regarding the development of therapeutic strategies against CRC.